Myanmar Agricultural Performance Survey (Dry Season 2024): Farm commercialization and farm services - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
 The security situation in Myanmar continues to negatively impact commercialization for crop farmers. During the monsoon season interview period (July–September 2024): a) Thirty-one percent of farmers reported feeling 'very insecure' or 'insecure'. b) Twenty-three percent expressed serious security concerns to move around in their village tract or township. c) Seven percent stated that conflict prevented the cultivation of some agricultural fields in their area. d) One percent reported land confiscation as a problem in their community. e) Eleven percent indicated fear of storing produce at home due to the risk of confiscation or destruction.  Security challenges for farming vary across states and regions, with the Delta area - the country's rice bowl - experiencing relatively better conditions.  Limited access to fuel, crucial for irrigation and mechanization among others, poses a significant constraint to farming. Nationally, about one-fifth and 40 percent of farmers reported either no or rare availability of fuel in their communities during the dry season and monsoon season of 2024 respectively. This situation during the monsoon is exacerbated in almost all of the states and regions, especially in the conflict-affected areas of Kayah, Shan, and Chin, with around 60 percent of the farmers reporting fuel scarcity.  Agricultural inputs were generally accessible during the 2024 dry season, indicating the resilience of the private sector in delivering these inputs. However, 5 percent of farmers reported unavailability of chemical fertilizers and seeds - a higher share than in the 2023 dry season - while 16 percent reported problems in securing agricultural labor.  Farmers in conflict-affected areas face more obstacles in farm commercialization, with agricultural inputs being much less available.  Input prices rose during the 2024 dry season compared to the same period in 2023. Mechanized plowing costs increased by 29 percent, while hired labor costs saw a rise of 33 percent for men and 32 percent for women. Urea prices experienced a modest increase of 3 percent. In the 2024 monsoon season, wages surged further compared to the preceding dry season, with men's wages rising by 16 percent and women's by 17 percent. These recent increases may be partly attributed to the introduction of the new Military Service Law.  Agricultural service delivery continues to decline, with fewer farmers able to access credit and agricultural extension services compared to previous years during the dry season of 2024.  All crop prices increased substantially compared to the previous dry season. While paddy prices increased by 14 percent, non-paddy crop prices increased significantly more.